Character Education as a Foundation for Moral Strengthening Based on Local Wisdom: an Analytical Study in Primary School Settings - Ulfah Rizki Afdilah; Try Gustaf Said; Nur Asmi; Muhammad Amin Said (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2025)
This study aims to analyze the implementation and influence of character education based on local wisdom on strengthening the morals of elementary school students. This study used a quantitative approach with an ex-post facto method. The sample in this study was selected through a purposive sampling technique. The research instrument was a Likert scale questionnaire whose validity and reliability have been tested. Data analysis was conducted using descriptive statistical techniques. The results of the study indicate that character education integrated with local cultural values is effective in instilling moral values in students. The distribution of moral value instillation dimensions in Grades 4 and 5 shows relatively even results across the three indicators, each ranging from 32 percent to 34 percent. The distribution of local wisdom-based character dimensions in both grades also shows a balanced proportion across the five indicators, namely between 19 percent and 21 percent. The frequency distribution shows that character indicators including independence, nationalism, religiosity, mutual cooperation, and integrity, as well as moral dimensions including moral values, beliefs, and identity, contribute equally to the formation of student morality.